Profile of children and adolescents with cancer diagnosed through the project stay tuned: it may be cancer in the City of Recife – PE (Research, Society and Development, 2021)
Childhood and adolescent cancer is considered a rare event when compared to adult cancer, accounting for about 1% to 3% of all cases. It comprises a heterogeneous group of pathologies that reach the age groups from 0 to 19 years, and is already considered the second cause of death among children and adolescents, second only to deaths from accidents and violence. The objective of this study was to identify the profile of children and adolescents with cancer diagnosed through the “Stay Tuned Project: it may be câncer” in a reference service in the city of Recife-PE, between 2015 and 2018. This is a quantitative study of the cross-sectional and documentary type of descriptive nature, and retrospective in nature. The sample will be composed of the medical records of patients of confirmed cases of cancer from September 2015 to December 2019, received for investigation through the Stay Tuned Project: it may be cancer. The project was submitted to the Ethics and Research Committee on Human Beings of the Hospital Complex/UPE with CAAE: 06177418.8.0000.5640. It was observed in the research data that in relation to the main complaints of referral to investigation of childhood cancer in the study sample, it was evidenced that pain (38.8%) was a major cause cited in the medical records. Given the above, it is possible to understand the importance of training PHC professionals, as they are the child's gateway to the SUS, and once properly trained makes it easier to observe the signs and symptoms in children and adolescents with cancer, providing early diagnosis.